ANALISIS VITAMIN C DAN KALIUM PADA DAUN BINAHONG (Anredera cordifolia (TEN) Steenis) - Endang Tri Wahyuni Maharani; Yusrin -; Ana Hidayati Mukaromah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Background: People already acknowledge binahong leaf because plant, namely root, stem, and leaf, have great use and benefit. Binahong leaf can be boiled or eaten freshly as salad. Nowadays binahong are packaged in capsules to make it easier to be consumed. Binahong leaf is used to cure several diseases such as stabilizing blood circulation and blood pressure; preventing stroke, uric acid, and maag; adding body immune; curing cough and bleeding, broken bone, all kinds of skin allergy, kidney infection, burnt scar, acne, and bleeding gum. All this time the use of binahong is based is based on experience, there has not been any scientific proof of the polyphenol, vitamin c, (as antioxidant), and Potassium found in binahong. Therefore, a research to find active substances on binahong is needed. Population of the Research: Sample of the research is binahong leaf taken from Karang Rejo Pentul Street RT 04 RW 02 Number 27 Semarang, about ± 2000 grams, dried in 25-27°C temperature for about 5 days and then made into powder.Result of the Research: The results of the research are: 1) Vitamin C amount found on binahong leaf is 6,76 ± 0,77 mg / 100 g; 2) The rate of potassium amount found on binahong leaf is 1,37 % b/bKeywords: analysis of vitamin C, Kalium, binahong leaf